Assessment of Knowledge Regarding HPV Vaccination among Medical Students - Baloch, Amna; Rind, Shumaila; Ghumro, Rashida; Ramzan, Shabana; Lashari, Shaista; Ali, Kainat (Indus Journal of Bioscience Research, 2025)
Background: The human papillomavirus, or HPV, is a serious worldwide public health issue since it has been connected to illnesses including cervical cancer. Although there are effective HPV vaccines available, medical students’ lack of knowledge may make it more difficult for them to encourage vaccination and lower the risks of HPV-related illnesses. Objective: This study aimed to assess the knowledge of HPV vaccination among medical students, identifying key areas of strength and weakness to inform targeted educational interventions. Methodology: A cross-sectional study was conducted from January to June 2023 at People’s University of Medical and Health Sciences for Women (PUMHSW), Nawabshah, Pakistan, involving 420 medical students. A standardized, self-administered questionnaire was used to gather data, and SPSS was used for analysis. Descriptive statistics and chi-square tests were used to look at relationships between knowledge levels and demographic characteristics. Results: The survey found that although most people (90%) were aware of HPV’s role in cancer and the advantages of vaccination (82.38%), fewer people (80.95%) were aware of the safety of vaccines. Age, academic year, and knowledge levels were shown to be significantly correlated; and older students (88.89%, p = 0.01) showed better knowledge. Compared to students in higher academic years, those in lower academic years, especially those in their first year (93.33%, p = 0.01), exhibited noticeably lower knowledge levels. Conclusion: While medical students possess strong awareness of HPV and vaccination benefits, gaps in knowledge regarding vaccine safety persist. Addressing these gaps through targeted educational interventions is essential to enhance HPV vaccination advocacy and public health outcomes.